Inflammatory characteristics of distinct abdominal adipose tissue depots relate differently to metabolic risk factors for cardiovascular disease: distinct fat depots and vascular risk factors - Kranendonk, Mariëtte E G; van Herwaarden, Joost A; Stupkova, Tereza; de Jager, Wilco; Vink, Aryan; Moll, Frans L; Kalkhoven, Eric; Visseren, Frank L J (Atherosclerosis, 2015)
Abdominal obesity is associated with insulin resistance and metabolic syndrome. However, specific contributions of distinct adipose tissue (AT) depots to metabolic complications of obesity are still unclear. In this study, the inflammatory profile of four distinct abdominal AT-depots and the relation between AT-characteristics and obesity-induced metabolic complications was evaluated. In 28 men undergoing abdominal aortic surgery, biopsies were collected from subcutaneous fat (SAT), and 3 visceral AT-depots: mesenteric (MAT), omental (OAT) and periaortic (PAT). The AT biopsies were characterized morphologically (adipocyte size, capillary density, CD68 + macrophages and crown-like-structures (CLS)) and the ex vivo adipokine secretion profile was determined by multiplex-immunoassay. The relation between depot-specific inflammatory characteristics and clinical parameters (waist circumference, insulin resistance and metabolic syndrome) was assessed by multivariable linear regression analysis. PAT contained the smallest adipocytes, highest capillary density and secreted abundant amounts of adipokines. SAT contained the lowest amount of macrophages and adipokines, while MAT and OAT displayed a similar inflammatory profile. In contrast to the other depots, MAT inflammation was most strongly related to metabolic complications of obesity, as adipocyte size and CLS were related to insulin resistance (β2.0; 95%CI1.15-2.85 and β0.24; 95%CI0.06-0.43) and MAT adipocyte size was associated with 79% higher odds of having metabolic syndrome (OR1.79; 95% CI1.13-2.89). There are significant differences in the inflammatory profile of distinct abdominal fat depots, of which MAT characteristics were mostly associated with metabolic complications of obesity. These findings suggest a differential contribution of AT-depots to systemic metabolic dysfunction which precedes type 2 diabetes and vascular diseases.